(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The Mother Tongue-Based Multilingual Education policy is complex from different perspectives. The policy poses challenges to instructional materials development, teachers’ training, and language instruction. Instructional materials are only available in few languages. Each classroom has the representation of several linguistic backgrounds. Classroom teachers are split on whether or not mother-tongue instruction is right for them and their students. This chapter represents the process that is used in collecting the data necessary in answering the main and specific problems stated in chapter 1. It includes the research design, respondents of the study, sampling, techniques, instrument used in the study, validation of the research instrument, construction of the instrument, and the statistical treatment of data used. The data gathered included information about the respondent’s gender, age, highest educational attainment, civil status, length of services, and position. The researchers will conduct this study to know the perceptions of teachers in using the mother tongue as a medium of instruction because many teachers today have many perceptions regarding this matter, such as how they can teach easily that will also be easy for their students to understand the lesson, how they can motivate their students to appreciate and be interested in the subject, and the benefits and hindrances of using mother tongue to teach students.